2007
DOI: 10.1002/anie.200701139
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Construction of Fluorescent J‐Aggregates Based on Hydrogen‐Bonded Perylene Dyes

Abstract: Luminous nanorods: The self‐assembly of core‐twisted perylene bisimide fluorophores (see structures) in nonpolar organic solvents is directed by hydrogen‐bonding interactions. This supermolecular concept resulted in one‐dimensional J‐aggregates with a fluorescence quantum yield of near unity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
335
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 465 publications
(351 citation statements)
references
References 37 publications
14
335
2
Order By: Relevance
“…It was reported that formation of N H⋅⋅⋅O hydrogen bonds between the imide hydrogen atoms and the carbonyl oxygen atoms would lead the stretching vibrations of N H and C O to lower wavenumbers. [36] Hereby, stretching frequencies at υ(N H) = 3153, 3034 cm −1 and υ(C O) = 1662 cm −1 in this FT-IR spectrum ( Figure S3, Supporting Information) indicate that intermolecular hydrogen bonds form between N H and C O groups in both commercial PDINH and self-assembled PDINH supramolecular systems. Such hydrogen bond interactions together with intermolecular π-π stacking interactions are proposed to influence the arrangement of PDINH molecules in self-assembled PDINH supramolecular system and stabilize the PDINH nanoassemblies.…”
Section: Doi: 101002/adma201601168mentioning
confidence: 89%
“…It was reported that formation of N H⋅⋅⋅O hydrogen bonds between the imide hydrogen atoms and the carbonyl oxygen atoms would lead the stretching vibrations of N H and C O to lower wavenumbers. [36] Hereby, stretching frequencies at υ(N H) = 3153, 3034 cm −1 and υ(C O) = 1662 cm −1 in this FT-IR spectrum ( Figure S3, Supporting Information) indicate that intermolecular hydrogen bonds form between N H and C O groups in both commercial PDINH and self-assembled PDINH supramolecular systems. Such hydrogen bond interactions together with intermolecular π-π stacking interactions are proposed to influence the arrangement of PDINH molecules in self-assembled PDINH supramolecular system and stabilize the PDINH nanoassemblies.…”
Section: Doi: 101002/adma201601168mentioning
confidence: 89%
“…[282,283] J-aggregates with significantly more red-shifted absorption (λ max = 642 nm) and emission bands (λ em = 654 nm) could be obtained from the same tetraphenoxy-bay-substituted PBI chromophore, but bearing N-H imide groups (PBI 7), by hydrogen-bond directed self-assembly via the imide subunits (Figure 20). [284] With a redshift of ≈2500 cm −1 compared to the monomer's absorption maximum, increased oscillator strength, high fluorescence quantum yield (≈85%), decreased fluorescence lifetimes (2.6 ns for the aggregate versus 6.8 ns for the monomers in MCH) as well as a dominant 0-0 transition with loss of vibronic progressions, aggregates of PBI 7 indeed fulfill all the desirable criteria of a J-aggregate. However, only moderate band narrowing and a still notable Stokes shift (albeit reduced compared to the respective monomers) are indicative of significant structural (static) disorder which was elucidated by temperature-dependent spectroscopy from 5 to 300 K. [285] The static disorder was attributed to the twisted PBI cores with variations in the orientation of the phenoxy bay-substituents and the presence of two different possibilities of cisoid or transoid hydrogen bonding patterns due to the presence of two carbonyl groups at each imide unit.…”
Section: Supramolecular Systems: Perylene Bisimide H-and J-aggregatesmentioning
confidence: 99%
“…Photoswitchable melamine 2 was thus studied for complexation with perylene bisimide dye 4 (Figure 4a), 23 which has a intriguing aggregation propensity to form slipped ππ stacked aggregates (J-aggregates). 24 Though 2 and 4 are both ditopic CMHB building blocks, these molecules coassemble not only at the 1:1 but also 2:1 molar ratio as shown by UVvis titration experiments (Figure 4b). Interestingly, the absorption band of the perylene dye showed a remarkable red-shift upon going from the 1:1 to 2:1 ratio, which is characteristic of the formation of J-aggregates.…”
mentioning
confidence: 94%